SA-FPN: An effective feature pyramid network for crowded human detection - Zhou, Xinxin; Zhang, Long (Applied intelligence (Dordrecht, Netherlands), 2022)
The crowded scenario not only contains instances at various scales but also introduces a variety of occlusion patterns ranging from non-occluded situations to heavily occluded cases, making the shapes of the instances different. All of those can result in human detectors being hard to apply to them. Feature pyramid networks (FPN), as an indispensable part of generic object detectors, can significantly boost detection performance involving objects at different scales. As a result, in this paper, we equip FPN with a multi-scale feature fusion technology and attention mechanisms to improve the performance of human detection in crowded scenarios. Firstly, we designed a feature pyramid structure with a refined hierarchical-split block, referred to as Scale-FPN, which can better handle the challenging problem of scale variation across object instances. Secondly, an attention-based lateral connection (ALC) module with spatial and channel attention mechanisms was proposed to replace the lateral connection in the FPN, which enhances the representational ability of feature maps through rich spatial and semantic information and lets detectors be capable of focusing on important features of occlusion patterns. Additionally, a bottom-up path augmentation (BPA) module was adopted to exploit the features of the Scale-FPN and ALC modules. To verify the effectiveness of the proposed method, we combined Scale-FPN, ALC and BPA, namely SA-FPN, and integrated it into the architecture of a crowded human detector. Experiments on the challenging CrowdHuman benchmark sufficiently validate the effectiveness of SA-FPN. Specifically, it improves the state-of-the-art result of CrowdDet from 41.4% to 39.9% M R - 2 , which indicates that the detector with SA-FPN brings in fewer false positives.